PARITAS IBU BERSALIN DAN LETAK JANIN DENGAN KEJADIAN KETUBAN PECAH DINI - Rachel Dwi Wilujeng (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2017)
Premature ruptured membranes are defined as rupture of the membranes before the onset of labor, regardless of gestational age Early ruptured membranes can be caused by parity and fetal location. The parity of multiparous mothers and grandemultipara is more at risk of developing a CDD than primiparous mothers. Whereas the abnormal fetal location is more at risk of occurring KPD than normal fetal lateness. The incidence of KPD in RS.UTS from 2012-2014 averaged 19.78% and was more than the number of KPD incidents. Based on this, a study was conducted which aimed to determine whether there was a relationship between maternal parity and the location of the fetus with the incidence of KPD in UTS Hospital 2015. Method: This study used a cross sectional design. Sampling by systematic random sampling with a sample of 110 people. Secondary data collection from labor registers at UTS Hospital. The results of the study were made frequency tables, cross tabulations and analyzed by Chi-Square test with the provisions of abel2 table 3.84 (? = 0.05). Results: From the results of the study, the majority of the mothers who experienced KPD were multiparous (52.38%) and the fetal location was abnormal (80.77%). Based on the results of the Chi-Square test on parity obtained ?2count> ?2table, 6.67> 3.84 and fetal location obtained 21.24> 3.84 so that H0 was rejected .. Discussion: From the results of the study it can be concluded that there is a relationship between parity maternity and the location of the fetus with the incidence of KPD. Therefore to reduce the incidence of KPDs, midwives should make early detection of pregnancy and counseling during pregnancy for married couples regarding safe parity for pregnancy and childbirth and are expected to be able to provide action on problems experienced by mothers in accordance with their authority, especially in the event of KPD .